WANPRESTASI DALAM PERJANJIAN SEWA BELI ELEKTRONIK, MESIN, DAN FURNITURE ( STUDI PADA UD. KARMA RAHAYU MANDIRI KLUNGKUNG ) - Rai Cahyadi Putra, Ida Bagus; Putra Atmadja, Ida Bagus; Wiratni Darmadhi, A. A. Sagung (Kertha Semaya : Journal Ilmu Hukum, 2013)
Wanprestasi of the lease agreement at UD. Karma Rahayu Klungkung used as areference in the practice of hire purchase agreement. It aims to determine the factors that lead toa default on UD. Karma Rahayu Mandiri Klungkung. In this study using empirical legalresearch. Of direct research and to obtain information from multiple informants in the fieldfound several factors that led to the event of default factors and the socio-economic situation ofthe buyer in bad faith.
Keywords: Agreements, Hire Purchase, Wanprestasi